Wt1 Positive dB4 Neurons in the Hindbrain Are Crucial for Respiration - Schnerwitzki, Danny; Hayn, Christian; Perner, Birgit; Englert, Christoph (Frontiers in Neuroscience, 2020)
Neuronal networks commonly referred to as central pattern generator (CPG) networks coordinate the generation of rhythmic activity like locomotion and respiration. These networks are proposed to exhibit a high degree of homology in their development. Their establishment is influenced by a variety of transcription factors. One of them is the Wilms tumor protein Wt1 that is present in dI6 neurons of the ventral spinal cord, which are involved in the coordination of locomotion. Here we report about the so far undescribed presence of Wt1 in neurons of the caudoventral medulla oblongata and their impact on respiration. By performing marker analyses, we were able to characterize these Wt1 positive (+) cells as dB4 neurons. The temporal pattern of Wt1 occurrence suggests a role for Wt1 in the differentiation of dB4 neurons during embryonic and postnatal development. Conditional knockout of Wt1 in these cells caused an altered population size of V0 neurons already in the developing hindbrain leading to a decline in the respiration rate in the adults. Thereby, we confirmed and extended the so far proposed homology between neurons of the dB4 domain in the hindbrain and dI6 neurons of the spinal cord in terms of development and function. Ablation of Wt1+ dB4 neurons resulted in the death of neonates due to the inability to initiate respiration suggesting a vital role for Wt1+ dB4 neurons in breathing. These results extend the role of Wt1 in the CNS and show that in addition to its function in differentiation of dI6 neurons it also contributes to the development of dB4 neurons in the hindbrain that are critically involved in the regulation of respiration.